2023
DOI: 10.1039/d2nr06055h
|View full text |Cite
|
Sign up to set email alerts
|

NiS2 nanoparticles by the NaCl-assisted less-liquid reaction system for the magnesium-ion battery cathode

Abstract: Rechargeable magnesium batteries are expected to be the next generation of energy storage devices. Therefore, it is of great significance to develop low-cost and long-life magnesium(Mg) electrode materials. However, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The b value represents the electrochemical reaction under the control of different behaviors, b = 0.5 indicates the typical diffusion control behavior, and b = 1 indicates that the contribution of the current is completely controlled by the surface. 32 As shown in Fig. 4h, the log ( v )–log ( i ) figure shows that the peak b values of the cathode and anode are −0.6525, −0.7143, 0.5864, and 0.9383, respectively.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The b value represents the electrochemical reaction under the control of different behaviors, b = 0.5 indicates the typical diffusion control behavior, and b = 1 indicates that the contribution of the current is completely controlled by the surface. 32 As shown in Fig. 4h, the log ( v )–log ( i ) figure shows that the peak b values of the cathode and anode are −0.6525, −0.7143, 0.5864, and 0.9383, respectively.…”
Section: Resultsmentioning
confidence: 72%
“…In the low-frequency region, the Nyquist diagram is almost a vertical line, which indicates that the electrode performance is not limited by the electrolyte diffusion process, which is a very ideal capacitive behavior. 32 The mechanism of the electrode reaction was studied by using in situ XPS. Fig.…”
Section: Papermentioning
confidence: 99%
“…For example, lithium metal forms needle-like dendrites during cycling that impede the electrochemical performance over time and pose a fire hazard owing to short cycle times. 10,11 Magnesium-sulfur (Mg-S) batteries are an emerging rechargeable battery technology designed to mitigate this safety issue.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, NiS 2 was identified as a viable candidate for fabricating positive electrodes for Mg batteries. 27 However, NiS 2 is anion-rich and exhibits a low electronic conductivity. 28 Fortunately, electrode materials are typically combined with highly conductive carbon-based materials to enhance their electrical conductivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a previous study, NiS 2 was identified as a viable candidate for fabricating positive electrodes for Mg batteries . However, NiS 2 is anion-rich and exhibits a low electronic conductivity .…”
Section: Introductionmentioning
confidence: 99%